Stock prices and economic fluctuations: a Markov switching structural vector autoregressive analysis - Markku Lanne; Helmut Luetkepohl (Center for Economic Studies and ifo Institute (CESifo), 2008)
The role of expectations for economic fluctuations has received considerable attention in recent business cycle analysis. We exploit Markov regime switching models to identify shocks in cointegrated structural vector autoregressions and investigate different identification schemes for bi-variate systems comprising U.S. stock prices and total factor productivity. The former variable is viewed as reflecting expectations of economic agents about future productivity. It is found that some previously used identification schemes can be rejected in our model setup. The results crucially depend on the measure used for total factor productivity.
Keywords: C32; 330; Cointegration; Markov regime switching model; vector error correction model; structural vector autoregression; mixed normal distribution; Konjunktur; Erwartungstheorie; Schock; Börsenkurs; Produktivität; Markovscher Prozess; VAR-Modell; Schätzung; USA